2015
DOI: 10.1002/dvdy.24284
|View full text |Cite
|
Sign up to set email alerts
|

Signals from the brain induce variation in avian facial shape

Abstract: Background How developmental mechanisms generate the phenotypic variation that is the raw material for evolution is largely unknown. Here we explore whether variation in a conserved signaling axis between the brain and face contributes to differences in morphogenesis of the avian upper jaw. In amniotes, including both mice and avians, signals from the brain establish a signaling center in the ectoderm (the Frontonasal ectodermal zone or “FEZ”) that directs outgrowth of the facial primordia. Results Here we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 58 publications
(68 reference statements)
3
60
0
Order By: Relevance
“…Our work adds to the known relationship between NCCs within the developing cranial midline and the ventral forebrain by demonstrating that a loss of cilia-dependent HH-responsiveness in NCCs correlated with ventral neuroectodermal widening. This work, in tandem with the work of others (Chong et al, 2012; Hu et al, 2015; Marcucio et al, 2005; Petryk et al, 2015), suggests that NCCs are involved in a bidirectional signaling cascade. Understanding the tissue of origin and timing of signals between NCCs and the brain will help unveil how these two organs coordinate their development.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our work adds to the known relationship between NCCs within the developing cranial midline and the ventral forebrain by demonstrating that a loss of cilia-dependent HH-responsiveness in NCCs correlated with ventral neuroectodermal widening. This work, in tandem with the work of others (Chong et al, 2012; Hu et al, 2015; Marcucio et al, 2005; Petryk et al, 2015), suggests that NCCs are involved in a bidirectional signaling cascade. Understanding the tissue of origin and timing of signals between NCCs and the brain will help unveil how these two organs coordinate their development.…”
Section: Discussionsupporting
confidence: 72%
“…The ventral forebrain serves as a SHH signaling center that can directly influence the behavior of NCC with in the facial midline (Chong et al, 2012; Hu et al, 2015; Marcucio et al, 2005). Increasing SHH in the ventral forebrain results in mid-facial widening, while abrogating a SHH signal produced a narrowed or collapsed mid-face, decreased proliferation of NCCs, and subsequently reduced the size of the facial prominences (Aoto and Trainor, 2015; Hu and Marcucio, 2009; Marcucio et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Breakthrough experiments in molecular genetics have shown that the mechanisms driving beak shape variation encompass modifications to the timing of expression of conserved developmental pathways (5-9), resulting in beak diversity described by a few relatively simple geometric transformations (10). However, pleiotropic associations between different skull structures can also contribute to the shape of the avian beak (11), and Sonic hedgehog signaling from the forebrain also relates to the spatial organization of, and changes to, face and beak shape (12)(13)(14). Furthermore, assessments of bird skull phenotypic variation suggest that beak morphology may evolve cohesively with cranial morphology (15,16).…”
mentioning
confidence: 99%
“…Shh expression in the avian embryos was detected by standard in situ hybridization resulting in the domain of interest being stained dark blue (Hu et al 2015; Chong et al 2012). 3D data of both this domain, as well as exterior surface of the avian embryo were acquired on Bioptonics 3000 OPT system (Sky Scan, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Here, we develop a morphometric method to quantify 3D shape variation in Sonic hedgehog (Shh) mRNA expression domains in avians (chickens and ducks) and explore relationships with embryonic facial shape. The focus here is on methods and a more thorough discussion of the experimental model and its biological context appears elsewhere (Hu et al 2015). …”
Section: Introductionmentioning
confidence: 99%